Comprehensive University Training from The Context of the Humanities and its Contribution to Experiential Learning for Service - Fajardo Pascagaza, Ernesto (2022)
This article aims to carry out a reflective and contextualized exercise on the transversal value of the humanities from its contribution to the comprehensive training processes of university students from its innovative contribution to experiential service learning. For this purpose, in this text some aspects that seek to support the role of the humanities in comprehensive university education and its correlation with experiential education for service are worked on. A reflective exercise is carried out on the relevance of comprehensive training and the teaching of the humanities in university institutions, to understand the opportune moment of higher education and the humanities as well as the establishment of the change in the way of thinking from the humanities. and its relationship with the teaching-learning process and its contribution to training for leadership and the new times, having as reference the guiding principles of comprehensive humanistic training, and its innovative contribution to service-oriented experiential learning. In this way, socioformation is used as the guiding pedagogical model of this reflection.